Age features of metabolism and cellular energy exchange in women - Pestryaeva L.A; Tretyakova T.B; Deryabina E.G; Dankova I.V; Kinzhalova S.V; Borisova S.V (LCC «Medicine-Inform», 2018)
Age features of metabolism and cellular energy exchange in women Pestryaeva L.A., Tretyakova T.B., Deryabina E.G., Dankova I.V., Kinzhalova S.V., Borisova S.V. Urals Research Institute of Maternity and Childhood, Ekaterinburg Aim: identification of the features of metabolism and cellular energy exchange in perimenopausal women. Patients and Methods: 2 groups of women were examined: I (control) - 25 women of reproductive age; II (main) - 25 women in perimenopause. At the time of examination, all the patients in the control group had a regular menstrual cycle. Menopause in patients of the main group was natural, began after 45 years. The duration of menopause in patients of the main group is from 1 to 3 years. 64% of patients in the main group had diseases associated with violation of neurohumoral regulation: dyskinesia of the gastrointestinal tract and biliary tract, neurocirculatory dystonia of hypertonic type, excess body weight and obesity (BMI>;25 kg/m2). At the time of examination, no exacerbation of chronic extragenital diseases was observed. In the main group, climacteric syndrome was detected in 56% of women, including moderate and severe degree. Biochemical examination of venous blood serum is performed on an automated analyzer with the help of unified test systems. The activity of enzymes of cellular energy exchange of succinate dehydrogenase and a-glycerophosphate dehydrogenase in lymphocytes was determined by the cytochemical method followed by visual morphometry. Results: age specific features of metabolism and cell bioenergetics (decrease in the activity of energy metabolism enzymes, an increase in the total protein, albumin, glucose, cholesterol, triglycerides, uric acid) in perimenopausal women were established. Conclusions: women in perimenopause have a lower activity of mitochondrial enzymes than women in reproductive age. During the period of menopause there is a decrease in cellular energy exchange and synthesis of sex hormones, as evidenced by the increase in the content of the main metabolites (total protein, albumin, glucose, cholesterol, LDL, triglycerides, uric acid). The study of processes of intracellular energy exchange at various stages of ontogenesis is a promising direction of scientific research, it is extremely important to maintain the reproductive potential and prevent old age diseases at the population level. Key words: perimenopause, menopause, metabolism, energy exchange, succinate dehydrogenase, a-glitserofosfatdegidrogenase. For citation: Pestryaeva L.A., Tretyakova T.B., Deryabina E.G. et al. Age features of metabolism and cellular energy exchange in women // RMJ. 2018. № 5(I). P. 16-18.